Transient third-degree atrioventricular block during anaesthesia in a cat - Hiroshi Sunahara (Tripoli University, 2021)
Background: Third-degree atrioventricular block is usually permanent, with transient cases being rare. Cats with transient third-degree atrioventricular block. It had been not reported in detail. Case Description: A 9.3-year-old, male shorthair cat was evaluated for possible nervous disease resulting from otitis interna. Under propofol and isoflurane anaesthesia, this cat developed a third-degree atrioventricular block. Isoproterenol was administered by continuous infusion to increase its heart rate. During recovery, heart rate returned to sinus bradycardia together with first-degree atrioventricular block without medical treatment. The cause of transient atrioventricular block was not observed at the examination. Conclusion: The case of this cat suggests that anaesthesia can result in a transient third-degree atrioventricular block.